The Effect of Weight Training Program at Club Langit on Vertical Jump Improvement in Volleyball Athletes - Virgie Naila Balqis; Gunawan; Sheva Ahmad Dzakiawan Putra Gusma; M.Arief Setiawan; Dany Aulia (Gladi : Jurnal Ilmu Keolahragaan, 2026)
This study aims to determine the effect of weight training programs on increasing vertical jump in volleyball athletes at Club Langit. Vertical jump is one of the important physical abilities in volleyball because it is directly related to performance when doing smashes, blocks, and serves. The method used in this study is a quasi-experimental method with a pretest-posttest group design. The subjects of the study were 12 volleyball athletes who participated in a weight training program for 4 weeks with a frequency of 3 times a week. The training program focused on strengthening the muscles of the legs, hips, and core muscles. The results of data processing showed a significant increase in vertical jump results after the training program was carried out, with an average increase of 18%. These results indicate that weight training can effectively improve vertical jump ability. The conclusion of this study is that the weight training program has a positive effect on increasing the vertical jump of volleyball athletes, so it is worthy of being part of a systematic and sustainable physical development program at Club Langit